Why Do Heterosporous Plants Have So Few Chromosomes? - Kinosian, Sylvia P.; Rowe, Carol A.; Wolf, Paul G. (Frontiers in Plant Science, 2022)
The mechanisms controlling chromosome number, size, and shape, and the relationship of these traits to genome size, remain some of the least understood aspects of genome evolution. Across vascular plants, there is a striking disparity in chromosome number between homosporous and heterosporous lineages. Homosporous plants (comprising most ferns and some lycophytes) have high chromosome numbers compared to heterosporous lineages (some ferns and lycophytes and all seed plants). Many studies have investigated why homosporous plants have so many chromosomes. However, homospory is the ancestral condition from which heterospory has been derived several times. Following this phylogenetic perspective, a more appropriate question to ask is why heterosporous plants have so few chromosomes. Here, we review life history differences between heterosporous and homosporous plants, previous work on chromosome number and genome size in each lineage, known mechanisms of genome downsizing and chromosomal rearrangements, and conclude with future prospects for comparative research.